Economic burden of pneumococcal disease in children in Liguria, Italy. Issue 5 (30th November 2022) - Amicizia, Daniela; Astengo, Matteo; Paganino, Chiara; Piazza, Maria Francesca; Sticchi, Camilla; Orsi, Andrea; Varlese, Federica; Hu, Tianyan; Petigara, Tanaz; Senese, Francesca; Prandi, Gian Marco; Icardi, Giancarlo; et al.
ABSTRACT: Vaccinations against Streptococcus pneumoniae are included in infant immunization programs globally. However, a substantial burden due to pneumococcal disease (PD) remains. This study aimed to estimate the cost of emergency department (ED) visits and hospitalizations associated with invasive pneumococcal disease, all-cause pneumonia, and acute otitis media in children <15 years of age in the Liguria region of Italy between 2012 and 2018. The retrospective cohort study used data from the Liguria Region Administrative Health Databases and the Ligurian Chronic Condition Data Warehouse, which contain information on hospital stays, outpatient visits, laboratory/imaging techniques, surgical procedures, and pharmaceutical prescriptions. Patients with one or more ED or inpatient claim for PD (based on International Classification of Diseases, Ninth Revision, Clinical Modification codes) were included. Cost of ED visits and hospitalizations were estimated from the diagnosis-related group system and procedures performed in the ED. In Ligurian children <15 years of age during 2012–2018, the median annual number of hospitalizations plus ED visits due to PD was 4, 009, and the median estimated annual cost was €3.6 million. All-cause pneumonia accounted for the majority of hospitalization costs during the study period. Number and costs of ED visits and hospitalizations increased from 2012 to 2018. Despite widespread infant immunization in Liguria, economic costs due to PD-associated ED visits and hospitalizations remained high in children 0–14 years of age.